2019
DOI: 10.1007/s40415-019-00525-2
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive H2O2 is involved in sorghum defense against aphids

Abstract: Reactive oxygen species (ROS) play a major role in plant defense against pathogens, but the evidence for their role in defense against insects is still limited. In this study, HN16 and its mutated line (asm1) were used as research objects, and the potential role of H 2 O 2 in sorghum against aphid was examined. Constitutive H 2 O 2 was considered the main factor associated with increased aphid tolerance, although aphid feeding also induced an increase in the H 2 O 2 concentration. By studying ROS scavenging en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 54 publications
1
11
1
Order By: Relevance
“…One of the reactions of plants to insect invasion is generation of ROS [49], and their accumulation contributes to plant's defense against aphids [50][51][52]. However, in our study, although genes related to superoxide metabolism was enriched in GO terms, no significant changes in ROS synthesis were observed in both antixenotic and antibiotic soybean during aphid infestation, but they were increased significantly in the susceptible genotype ( Figure 7).…”
Section: Discussioncontrasting
confidence: 50%
“…One of the reactions of plants to insect invasion is generation of ROS [49], and their accumulation contributes to plant's defense against aphids [50][51][52]. However, in our study, although genes related to superoxide metabolism was enriched in GO terms, no significant changes in ROS synthesis were observed in both antixenotic and antibiotic soybean during aphid infestation, but they were increased significantly in the susceptible genotype ( Figure 7).…”
Section: Discussioncontrasting
confidence: 50%
“…Research on resistant wheat cultivars showed a higher level of CAT than in cultivars susceptible to heat stress [68]. Plant cultivars resistant to phytophagous showed higher CAT activity than sensitive cultivars [69,70].…”
Section: Discussionmentioning
confidence: 92%
“…Consistent with this pattern, in a comparison of sorghum genotypes that were resistant or susceptible to the phytotoxic sugarcane aphid (M. sacchari), aphid challenge on resistant plants induced an earlier oxidative response that peaked at 3 days and then declined, whereas H 2 O 2 levels in the susceptible cultivar initially decreased in response to aphids and then increased at 12 days post-infestation, when extensive aphid damage was present (Pant and Huang, 2021). However, heightened H 2 O 2 levels have also been observed in an aphid-resistant chili pepper cultivar 6 days after challenge with avirulent green peach aphids even when aphids were removed 3 days prior (Sun et al, 2020); furthermore, a sorghum genotype resistant to the sugarcane aphid was reported to have constitutively high H 2 O 2 in comparison to a susceptible genotype even in the absence of infestation (Shao et al, 2019). Therefore, certain incompatible interactions also appear to involve long-term ROS accumulation.…”
Section: When Are Reactive Oxygen Species Produced In Response To Aph...mentioning
confidence: 99%
“…In the S cultivar, H 2 O 2 in infested plants decreased relative to uninfested controls at 3, 6, and 9 days, and increased at 12 days. M. sacchari (Shao et al, 2019)…”
Section: Sorghum Bicolor Poaceaementioning
confidence: 99%
See 1 more Smart Citation